Legal Certainty for the Implementation of Execution in the Form of Payment of Money in Lieu of Corruption Cases in the Criminal Justice System - Erwinda Emran, Nevertiti; Lina, Ramlani; Ismed, Mohamad (Riviera Publishing, 2024)
The determination of additional punishment in the form of